Mapas afetivos táteis: vivências urbanas não visuais na cidade de Fortaleza - Martins, Ana Kristia da Silva (2015)
This paper aims to study the way visually impaired people feel, think and act in the city of Fortaleza. The impairment has been considered as a social subject and not only as a sensorial restriction. Based on the theoretical inputs of social and environmental Psychology, this work considers the individual as a historical, social and emotional being, who establishes a relationship with his/her physical and social environment, transforming it and being transformed by it. This study questions the impact of the urban experiences from visually impaired people as emotional intensifiers (or not) of their actions in the city. The affective theory and the concept of esteem of place have guided the comprehension of the individuals’ relationship with the city, inclusively guiding us in the choice of the study methodology.By applying the generator instrument of affective maps (Bomfim, 2003), we proposed the construction of tactile images of the city, using molding and assembly materials, such as cotton, straws, strings, play dough and others. Thirty-seven visually impaired people with complete and partial blindness, from both genders, were consulted. The results indicated the construction of four images of the city of Fortaleza: Insecurity,Contrast, Destruction and pleasantness. The bad conditions on architectural and attitude accessibility in Fortaleza were emphasized as elements that cause much more insecurity to the contestants than the violence or the crime rate, causing a fear of moving through the city. Despite of the high occurrence of disempowering feelings, the respondents also identified positive aspects on their experiences, which are especially connected with the taste for public places, such as beaches and shopping malls; and for intimacy places, that are part of the contestants’ daily experiences and with social living with close friends and other in habitants of the city. The study concludes that the abundance of information which was gotten by the non-visual references allows us to have a full understanding of the city, even though the research had highlighted that the contestants have specific comprehensions and needs in relation to the urban environment, that are not fulfilled on Fortaleza, since the negative esteem of place has obtained more answers than the positive esteem of the place.